Answer: Hello, I saw another picture and i think it was A
Step-by-step explanation: Vertical Line test will determine if a graph is a function or not
Answer:
The distance between the two train stations is 1728 km
Step-by-step explanation:
The speed of the bus = 54 km/h
The speed of the truck = 48 km/h
When the bus and truck meet again, the distance covered by the bus = 216 km more than he distance traveled by the truck
Let the distance between the two train stations = x
Let the location where they first meet be y from station A we have;
The location where they meet again = y - 216 km
Therefore, we have;
Location where they
The time for the truck and the bus to meet again = t
Therefore, 54 × t - 48 × t = 216 km
6·t = 216 km
t = 36 hours
Therefore, the time for the bus to travel x + 216 km = 36 hours
54 × 36 = 1944 = x + 216
x = 1944 - 216 = 1728 km
The distance between the two train stations = 1728 km.
Answer:
The area of square in terms of x = 16x² -24x + 9
Step-by-step explanation:
It is stated in the question that the length of a square = 4x - 3
Formula to find the area of the square is
<h2 /><h2>Area = length²</h2><h2 />
Area = ( 4x - 3 )²
<em>by using ( a - b )² = a² + b² - 2ab</em>
here a = 4x and b = -3
So,
(4x)² + (-3)² - 2(4x)(3)
16x² + 9 - 2(12x)
16x² + 9 - 24x
16x² -24x + 9
The area of square in terms of x = 16x² -24x + 9
Use order of operations for this
4x+17=23
Move the 17 to the 23
4x=23-17
Then move the 4 over leaving the x by itself
X=6/4
X=1.5
Answer:
centre = (- 3, - 2) , radius = 1
Step-by-step explanation:
The equation of a circle in standard form is
(x - h)² + (y - k)² = r²
where (h, k) are the coordinates of the centre and r is the radius
Given
x² + 6x + y² + 4y + 12 = 0 ( subtract 12 from both sides )
x² + 6x + y² + 4y = - 12
Use the method of completing the square on the x and y terms
add ( half the coefficient of the x/ y terms )² to both sides
x² + 2(3)x + 9 + y² + 2(2)y + 4 = - 12 + 9 + 4
(x + 3)² + (y + 2)² = 1 ← in standard form
with centre = (- (- 3), - (- 2)) and r² = 1, that is
centre = (- 3, - 2) and radius = 1